2018
DOI: 10.1002/arco.5155
|View full text |Cite
|
Sign up to set email alerts
|

What happened after the Last Glacial Maximum? Transitions in site use on an arid inland island in north‐western Australia

Abstract: The presence of Aboriginal people in interior refuges as climate conditions deteriorated with the onset of glacial aridity is now well documented in the Australian arid zone. Further excavation at Yurlu Kankala, a large rock shelter located on an island of high land in the inland Pilbara, demonstrates repeated human occupation from at least 47-43 cal ka BP through the Last Glacial Maximum to the mid-Holocene. Despite the continued presence of bone representing human food remains and an increased occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…) and Yurlu Kankala (Reynen et al . ), have been argued to be LGM refuges because of their location near water, making them more productive than lowland areas. It seems that at Riwi there were also times when sufficient water was available for it to be occupied during an otherwise arid phase.…”
Section: Discussionmentioning
confidence: 99%
“…) and Yurlu Kankala (Reynen et al . ), have been argued to be LGM refuges because of their location near water, making them more productive than lowland areas. It seems that at Riwi there were also times when sufficient water was available for it to be occupied during an otherwise arid phase.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed Veth (2014) suggested that “such datasets…are being used as a mainstream proxy to explore archaeological trends and specifically demographic fluctuations” for some regions of Australia. Hence, the purpose and some of the key limitations of such modelling have been overlooked, with the end effect that the results may be uncritically treated as fact (e.g., Brockwell et al, 2017; Cook, 2019; Kusaka et al, 2018; Lancelotti et al, 2016; Lopez et al, 2019; McDonald, 2016; McDonald et al, 2018; Reynen et al, 2018; Tibby et al, 2018; Zeanah et al, 2017) and even used as foundational premises of further demographic frequency analysis. We explore some of these radiocarbon age‐based studies and some of their underlying premises below.…”
Section: Archaeology's Grand Challenges and The Role Of “Big Data”mentioning
confidence: 99%
“…It is proposed that at times of climatic or resource stress, people tended to migrate to isolated locations, termed refugia, where water and other resources were more reliable (Langley, 2014; Smith, 2013; P. M. Veth, 1993; see also Reynen et al, 2018 and references therein). Upland ranges, lowland riverine and gorge systems, separated from sand‐ridge deserts, are argued to have been particularly important refugia for human survival during the LGM.…”
Section: The Australian Radiocarbon Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst most of these in-house operations are now essentially shut down, many academics have hybridised their working modelsundertaking CHM projects that align with research interests, often connected by region, Traditional Owner group, or client, and CHM data is increasingly being used in academic archaeological research (e.g. Reynen et al 2018;Slack et al 2020). The development of genuine relationships with communities then remains a complex one faced by all archaeologists, and without active projects in a given region, the short duration of a funded project cannot be denied.…”
Section: Sam Harpermentioning
confidence: 99%